Current status and recent trend of irrigation water use in China. (14th April 2020) - Han, Songjun; Tian, Fuqiang; Gao, Long
ABSTRACT: China's irrigation water use witnessed a continuously increasing trend from 1949 to 1990, while it has begun to show a decreasing one with fluctuations since then. During 2003–2013, the amount of agricultural water use, of which over 95% is for irrigation, increased to a peak value of 392 × 10 9 m 3 . In 2017, it decreased to 377 × 10 9 m 3 and accounted for 62.3% of total water use for the whole of China. It can be concluded that irrigation water use has reached its limit in China. In the northern part of China, the water scarcity situation sets a cap on irrigation water use, which will have further competition from environmental water use. In the southern part of China, the limited amount of irrigable land sets a cap on irrigation water use, which will have further competition from urbanization. Water‐saving policies and high‐efficiency irrigation technologies have been adopted by the Chinese government as the national strategy for sustainable irrigation water use. The challenges of irrigation development faced by China are increasing water productivity to reduce water consumption in north‐west China, reducing groundwater exploitation to restore aquifers in north China, increasing food production to ensure national food security in north‐east China, and promoting water conservation to control pollution in the southern part of China. © 2020 John Wiley & Sons, Ltd. Résumé: La consommation d'eau d'irrigation de la Chine a connu une tendance à la hausse continue entre 1949 et 1990, alors qu'elle commençait à montrer une tendance à la baisse avec des fluctuations depuis lors. En 2003–2013, la quantité d'eau utilisée par l'agriculture, dont plus de 95% est destinée à l'irrigation, a atteint une valeur maximale de 392 × 109 m 3 . En 2017, elle a diminué à 377 × 109 m 3 et occupé 62, 3% de l'utilisation totale d'eau pour l'ensemble de la Chine. On peut en conclure que l'utilisation de l'eau d'irrigation a atteint sa limite en Chine. Dans les régions septentrionales, la situation de pénurie d'eau fixe le plafond d'utilisation de l'eau d'irrigation, qui sera de surcroît concurrencé par l'utilisation environnementale de l'eau. Dans les régions méridionales, le peu de terres irrigables limite l'utilisation de l'eau d'irrigation, qui sera concurrencée par l'urbanisation. Le gouvernement chinois a adopté des politiques d'économie d'eau et des technologies d'irrigation à haute efficacité énergétique en tant que stratégie nationale d'utilisation durable de l'eau d'irrigation. Les défis du développement de l'irrigation auxquels la Chine est confrontée sont l'augmentation de la productivité de l'eau pour réduire la consommation d'eau dans le nord‐ouest de la Chine, réduire l'exploitation des eaux souterraines pour restaurer les aquifères dans le nord de la Chine, augmenter la production alimentaire pour assurer la sécurité alimentaire nationale dans le nord‐est de la Chine et promouvoir la conservation de l'eau pour lutter contre la pollution dans le sud de la Chine. © 2020 John Wiley & Sons, Ltd.